2012
DOI: 10.1089/neu.2011.2053
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Prevents Disruption of the Blood–Brain Barrier after Traumatic Brain Injury

Abstract: Significant effort has been focused on reducing neuronal damage from post-traumatic brain injury (TBI) inflammation and blood-brain barrier (BBB)-mediated edema. The orexigenic hormone ghrelin decreases inflammation in sepsis models, and has recently been shown to be neuroprotective following subarachnoid hemorrhage. We hypothesized that ghrelin modulates cerebral vascular permeability and mediates BBB breakdown following TBI. Using a weight-drop model, TBI was created in three groups of mice: sham, TBI, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…22) BBB damage, which is induced by cerebral ischemia, is associated with the multiple impairment such as TJ opening between microvascular endothelial cells (BMECs), neurons disruption and so on. 23) Therefore, we also detected the opening of TJ by TEM (Fig. 4) Arrows as shown in figure, a series of electronically dense bands were exhibited in TJ, which are located between adjacent plasma membranes and enclose cell cleavage.…”
Section: Resultsmentioning
confidence: 87%
“…22) BBB damage, which is induced by cerebral ischemia, is associated with the multiple impairment such as TJ opening between microvascular endothelial cells (BMECs), neurons disruption and so on. 23) Therefore, we also detected the opening of TJ by TEM (Fig. 4) Arrows as shown in figure, a series of electronically dense bands were exhibited in TJ, which are located between adjacent plasma membranes and enclose cell cleavage.…”
Section: Resultsmentioning
confidence: 87%
“…Our findings reveal a striking complexity in the evolution of AQP4 expression and localization from the acute (3 days) to the chronic phase (14-28 days) that may shed light on apparent contradictions within the existing literature. Prior studies, which have generally evaluated global AQP4 expression by western blot or gross scoring of immunohistochemical staining, have alternately reported that moderate TBI causes both reduced 16,17,20,23 and elevated 14,15,18,19,[21][22][23][24][25]37 AQP4 expression. In the present study, we observed both elevations and reductions in AQP4 expression depending upon the tissue and the element of the tissue subjected to analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies, AQP4 expression was most commonly evaluated globally, either by Western blot [14][15][16][17][18][19][20][21] or by grading of immunohistochemical staining after TBI. [21][22][23][24] We first quantified changes in global AQP4 expression within the cortex and striatum after mild and moderate TBI. After both mild and moderate TBI, a slight increase in global AQP4 expression was apparent both in the cortex ( Figure 5D) and in the striatum ( Figure 5J) that appeared to peak 7 days post injury, then subside over the subsequent 3 weeks.…”
Section: Evolution Of Aqp4 Dysregulation After Mild and Moderate Tbimentioning
confidence: 99%
“…Ghrelin is also known to have binding capacity at the endothelial cells of BBB [18]. Recently, it was reported that ghrelin prevents BBB disruption after traumatic brain injury [19,20]. The report by Kwan et al [21] showed that ghrelin decreases lipopolysaccharideinduced microvascular leak during inflammation.…”
Section: Introductionmentioning
confidence: 99%